Error Analysis on Student's Grammar in Writing Descriptive Text at Grade VIII of SMP Gajah Mada - Madina; Hanna Sabrina Rahayu Pardede; Ester Yunita Hutasoit (International Journal of Integrative Sciences, 2024)
The ability to use proper grammar is essential for effective communication, writing and conveying ideas accurately. Therefore, in this research we will apply a student’s grammatical writing errors in descriptive text. The research carried out was a class action. The results showed that the most common mistakes more negligence in writing descriptive text, which was related to low motivation and lack of understanding of the text. The discussion concluded that most students still had difficulty writing descriptive texts due to a lack of understanding of grammar and present simple tense. It is recommended that students improve their understanding of English by reading more books, practicing writing, and expanding, their vocabulary